The Role of Librarians in Children's Digital Literacy in The Pekalongan District Public Library - Qotrunnada, Alisha Ainaya; Azizah, Ika Nur (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2025)
Background of the study: The use of digital devices such as computers in the library by children needs to be controlled and supervised so as not to have a negative impact on children. So the role of librarians is needed to carry out such control and supervision. Purpose: The aim of this study is to determine the role of librarians in children's digital literacy at the Pekalongan District Public Library. Method: The research method used is qualitative with a case study approach. Data collection through semi-structured interviews and documentation was carried out for 15 days in the period from January 24 to February 10, 2025.  Findings: Librarians at the Pekalongan Regency Public Library play a role as learning supporters through guidance on the use of digital devices, teaching through digital displays, controlling the use of digital devices in the form of computers in the library, and providing digital library recommendations to parents Conclusion: Although librarians play a role in supporting children's digital literacy in the library, it is necessary to develop their role through skills development by participating in broader training through collaboration with external parties.    Keywords: Children digital literacy, digital literacy, librarian, librarian role, public library --------------------------------------------------------------------------------------------------------------------------------------------------------------------- AbstrakPeran Pustakawan Dalam Literasi Digital Anak di Perpustakaan Daerah Kabupaten Pekalongan  Latar Belakang: Penggunaan perangkat digital berupa komputer di perpustakaan oleh anak-anak perlu dilakukan pengawasan agar tidak memberikan dampak negatif pada anak. Sehingga, dibutuhkan peran pustakawan untuk melakukan pengawasan tersebut. Tujuan: Penelitian ini bertujuan untuk mengetahui peran pustakawan dalam literasi digital anak di Perpustakaan Daerah Kabupaten Pekalongan. Metode: Metode penelitian yang digunakan yakni kualitatif dengan pendekatan studi kasus. Adapun pengumpulan data melalui wawancara semi-terstruktur dan dokumentasi dilakukan selama 15 hari dalam rentang waktu 24 Januari-10 Februari 2025. Temuan: Pustakawan di Perpustakaan Daerah Kabupaten Pekalongan melakukan peran sebagai pendukung pembelajaran melalui pembimbingan penggunaan perangkat digital, melakukan pengajaran melalui tayangan digital, mengontrol penggunaan perangkat digital berupa komputer di perpustakaan, dan memberikan rekomendasi perpustakaan digital kepada orang tua. Kesimpulan: Meskipun pustakawan melakukan peran untuk mendukung literasi digital anak di perpustakaan, perlu dilakukan pengembangan peran melalui pengembangan keterampilan dengan mengikuti pelatihan yang lebih luas melalui kerja sama dengan pihak eksternal. Kata Kunci: Literasi digital, literasi digital anak, perpustakaan umum, peran pustakawan, pustakawan